A new approach to detect epistasis utilizing parallel implementation of ant colony optimization by MapReduce framework. Issue 3 (3rd March 2016) - Zhou, Zhihui; Liu, Guixia; Su, Lingtao
Abstract : Genome-wide association studies (GWAS) involve the detection and interpretation of epistasis, which is responsible for the 'missing heritability' and influences common complex disease susceptibility. Many epistasis detection algorithms cannot be directly applied into GWAS as many combinations of genetic components are present in only a small amount of samples or even none at all. For a huge number of single nucleotide polymorphisms and inappropriate statistical tests, epistasis detection remains a computational and statistical challenge in genetic epidemiology. Here, we develop a novel method to identify epistatic interactions related to disease susceptibility utilizing an ant colony optimization strategy implemented by Google's MapReduce platform. We incorporate expert knowledge used to guide ants to make the best choice in the search process into the pheromone updating rule. We conduct sufficient experiments using simulated and real genome-wide data sets and experimental results demonstrate excellent performance of our algorithm compared with its competitors.